IMPLEMENTASI MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA (UPEJ Unnes Physics Education Journal, 2012)
Process Oriented Guided Inquiry Learning (POGIL) is an active learning model that uses learning in teams, guided inquiry activities to develop knowledge, questions to enhance critical thinking and analytical skills, problem solving, report, metacognition, and individual responsibility. The purpose of this study was to determine the increases of students' critical thinking skills through implementation of the model POGIL on the subject of heat. The study design using the Control Group Pre Test-Post Test. Samples were taken by simple random sampling technique. The results are POGIL can enhance students' critical thinking skills, with a value of 0.69 gain. Aspects of critical thinking that could be improved is aspects hypothesize, analyze and conclude. Based on the obtained test 75.00% of students categorized as very critical, critical category 18.75% and 6.25% of students categorized as critical enough. While the results based on observations obtained 18,75 % of students categorized as critical, and 81,25 % categorized as enough critical. The average value of the students psychomotor 90.89 and affective 87.11. The conclusions of this study is POGIL can enhance students' critical thinking skills in the subject of heat.